Olena Yakivna Goncharova (to the 100th anniversary of her birth) - Golubeva, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The article deals with the 100th anniversary of the birth of a famous scientist in the field of orthopaedics and traumatology, Prof. Olena Yakivna Goncharova (1911–1982).